As onomotopéias de Drummond (Filologia e Linguística Portuguesa, 2005)
The onomatopoiec production is a kind of phonological creation properly speaking or specific. Drummond uses pure and lexical onomatopeia in his poetic work. Some of his onomatopeia is so rich that often takes the place of words and explanation. There is also onomatopeia imitating impact, destruction, insect buzz, and so on.